ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI GAGAL LELANG PENGADAAN BARANG DAN JASA PEMERINTAH SECARA ELEKTRONIK ( E-PROCUREMENT ) DI KABUPATEN BADUNG - Karyasa, I N. R.; Salain, I M. Alit K.; Nadiasa, Mayun (JURNAL SPEKTRAN; vol 2, No 1, Januari 2014, 2014)
Starting in 2012 implementation of the procurement of goods / services in Badung regency have been conducted electronically (e-Procurement) by E-tendering procedure. But implementation in construction work package there were many failed auctions. This study aims to find out what factors that affect occurance of failed auction and what dominant factors influence it. The sample used in this study were 50 contractor company by using non-probability sampling with purposive sampling and data collection by using questionnaires. Data analysis was performed with factor analysis.   The results shows there are 5 factors that have affect to the occurrence of failed auctions, the procurement with cumulative variance 84.327% that from 30 variable. The most dominant factors is I factor with eigenvalues 7.818 and variance 26.061% that formed by 8 variables. The eight variables compiler of I factor that are, not yet ready with the procurement of goods /service electronically, fail to upload offering documents, the lack of time availability to prepare offering documents, late to know auction announcement, personnel qualifications of project team do not match, ther is no / in-appropriate support from suppliers, incomplete offering documents and do not ready with evidence of qualifications.
Keywords: Failed Auction, E-Procurement, E-tendering, Construction Work